Poetic Phenomenology in Thierry De Mey's Screendances: Open Corporealities, Responsive Spaces, and Embodied Experiences - Walon, Sophie (The International Journal of Screendance, 2014)
De Mey’s screendances are often praised for the extreme precision of their composition and framing, their dazzling editing, and their highly musical qualities. This undeniable technical virtuosity largely explains why his films often bewitch and hypnotize their spectators. However, the critical emphasis on this particular facet of his screendances portrays them as only being concerned with artful creativity, (over)stylization, and aesthetic perfection: through this lens, his films are seen merely as an expression of brilliant formalism. In this essay, I will try to point out another aspect of De Mey’s films (including his collaborations with choreographers such as Anne Teresa De Keersmaeker) as constructing a poetic vision of the world in which bodies and spaces closely interact and entwine.